2021
DOI: 10.1186/s12885-021-08349-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety of systemic anti-cancer treatment in oncology patients with non-severe COVID-19: a cohort study

Abstract: Background The viral pandemic coronavirus disease 2019 (COVID-19) has disrupted cancer patient management around the world. Most reported data relate to incidence, risk factors, and outcome of severe COVID-19. The safety of systemic anti-cancer therapy in oncology patients with non-severe COVID-19 is an important matter in daily practice. Methods ONCOSARS-1 was a single-center, academic observational study. Adult patients with solid tumors treated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(37 reference statements)
0
4
0
2
Order By: Relevance
“…One global systematic review that identified 38 different categories of delays and disruptions reported that clinician- or system-related variables, such as medicine stockouts or shortages of devices, personal protective equipment, and laboratorial or imaging tests, were the most frequently reported structural or process-related factors associated with delay . Several single-institution reports and surveys of physicians revealed that there were more treatment delays among patients infected with SARS-CoV-2 compared with patients who were not infected . Our analysis is the first study, to our knowledge, to identify systemic delays or cancellations in cancer treatment for a cohort of patients who were all diagnosed with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…One global systematic review that identified 38 different categories of delays and disruptions reported that clinician- or system-related variables, such as medicine stockouts or shortages of devices, personal protective equipment, and laboratorial or imaging tests, were the most frequently reported structural or process-related factors associated with delay . Several single-institution reports and surveys of physicians revealed that there were more treatment delays among patients infected with SARS-CoV-2 compared with patients who were not infected . Our analysis is the first study, to our knowledge, to identify systemic delays or cancellations in cancer treatment for a cohort of patients who were all diagnosed with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 86%
“… 16 Several single-institution reports and surveys of physicians revealed that there were more treatment delays among patients infected with SARS-CoV-2 compared with patients who were not infected. 17 , 18 Our analysis is the first study, to our knowledge, to identify systemic delays or cancellations in cancer treatment for a cohort of patients who were all diagnosed with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En nuestra cohorte, aproximadamente 6% de los pacientes que realizaban tratamiento activo, desarrolló infección por COVID-19, consistente con la tasa reportada en otros estudios 9 . De este modo, la gran mayoría de los tratados en el Centro de Infusión durante la pandemia, transcurrieron el periodo de estudio sin desarrollar infección por COVID-19.…”
Section: Discussionunclassified
“…La QMT comprende un grupo diverso de fármacos con diversos mecanismos de acción, lo cual hace difícil obtener conclusiones inequívocas respecto a su rol en el riesgo de infección. Sin embargo, numerosos estudios han evaluado esta asociación y existe evidencia creciente que establece la falta de asociación entre QMT y mayor riesgo infección o de mortalidad por COVID-19, respaldando la seguridad de continuar la infusión de estos tratamientos durante la pandemia [7][8][9] .…”
Section: Discussionunclassified